Phylogeny of the bristle worm family Eunicidae (Eunicida, Annelida) and the phylogenetic utility of noncongruent 16S, COI and 18S in combined analyses - Zanol, Joana; Halanych, Kenneth M.; Struck, Torsten H.; Fauchald, Kristian (Molecular Phylogenetics and Evolution, 2010)
The bristleworm family Eunicidae is distributed worldwide and well-known for the large size of many of its species, its hard jaws and its economic importance in the bait industry. Monophyly of Eunicidae has been contradicted in previous molecular and morphological phylogenetic analyses focusing on Eunicida or on its type genus, Eunice. The current study focused on the phylogeny of the family per se combining mitochondrial and nuclear genes in different analyses. It recovered well-resolved phylogenetic hypotheses supporting the monophyly of Eunicidae and Palola, the only monophyletic genus among the genera for which we tested their monophyly (Eunice, Marphysa, Palola, Lysidice and Nematonereis). Four other stable clades containing the type species of different genera, or species deemed very similar to them, were recovered within Eunicidae. These clades may represent monophyletic redefinitions of current genera, except for Eunice, and of previous synonymized genera. Evolution of the number of peristomial cirri and prostomial appendages in Eunicidae happened by independent step-by-step reduction in the opposite order of their ontogenetic development, suggestive of sequential heterochrony. All three genes were informative, however, at different levels within the combined trees. 16S and COI were important in recovering a monophyletic Eunicidae and relationships within the family, while 18S was important in the resolution of basal eunicidan relationships, monophyly of Onuphidae and basal relationships within this family. Moreover, results of congruence tests (SH and WRST using PABA) indicate that hidden support is picked up in the combined analyses, which is not revealed in the single gene analyses. Further supporting the idea that congruence is not a requirement for combining different partitions.
World Polychaeta Database (WPolyDb)